THE INFLUENCE OF ACCOUNTABILITY IN VILLAGE FUND MANAGEMENT ON THE ECONOMIC REPORT OF THE COMMUNITY IN FAFOE VILLAGE, MALAKA DISTRICT - Marisa S. B Seran; Hendrik Toda; Melkisedek N B C Neolaka; Maria L Lino (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of accountability in Village Fund management on the economy of the community in Fafoe Village. This study uses a quantitative approach with a survey method. The study population was the entire community of Fafoe Village, totaling 2,664 people, with a sample of 348 respondents determined using the Slovin formula and purposive sampling technique . Data collection techniques were carried out through a questionnaire with a Likert scale of 1-5 which had been tested for validity and reliability. Data analysis used simple linear regression analysis with the help of SPSS. The results showed that the accountability in Village Fund management was in the moderate category (average 2.42) and the community's economy was in the moderate category (average 2.28). The results of the hypothesis test show that accountability in managing Village Funds has a positive and significant effect on the community's economy (t count 5.104</ t table 1.967 significance 0.000 <0.05. The coefficient of determination (R²) value of 0.800 indicates that accountability in managing Village Funds is able to explain 80% of the variation in the community's economy, while the remaining 20% is explained by other variables outside the study. This study concludes that increasing accountability in managing Village Funds will be followed by an increase in the economy of the Fafoe Village community.